Clinical progression of COVID-19 coinfection in people living with the human immunodeficiency virus: scoping review - Diego Schaurich; Oclaris Lopes Munhoz; Angelo Ramos Junior; Angelica Dalmolin; Gabriela Oliveira; Luiza Cremonese (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to map the production of scientific knowledge on the clinical progression of COVID-19 coinfection in people living with the human immunodeficiency virus (HIV). Methods: scoping review, with search strategies in MEDLINE, Scopus, Embase, Web of Science, and LILACS. Dual independent data extraction and analysis of the material with similarity compilation and narrative synthesis. Results: sample consisted of 35 articles. Fever, cough, and dyspnea were the most prevalent signs/symptoms. Recurrent complications involved desaturation/worsening of oxygen desaturation and pneumonia. No standard pharmacological treatment was identified, and the main interventions involved the provision of supplemental oxygen and mechanical ventilation. The studies recommended preventive, care, and pharmacological practices. Conclusions: the clinical manifestations, complications, and treatments/assistance care for people coinfected with SARS CoV-2/HIV are similar to those of the general population. Coinfection, overall, does not infer a worse prognosis.